Efektivitas Program Peningkatan Diversifikasi dan Ketahanan Pangan Masyarakat Melalui Kegiatan Pekarangan Pangan Lestari (P2L) pada Kelompok Wanita Tani di Kota Tangerang Selatan - Fadia Pramesti; Dini Gandini Purbaningrum (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Sustainable Food Yard (P2L) is one of the priority programs in maintaining community food security. However, in the implementation of the program there are still problems, including the late delivery of assistance which has an impact on the delay in the implementation of activities so that the P2L program does not run in accordance with the technical instructions that have been issued each year, and assistance that is less than optimal. The purpose of this study was to determine and analyze the effectiveness of the program to increase diversification and community food security through sustainable food yard activities (P2L) in farm women's groups in South Tangerang City. The method in this research is a qualitative approach with descriptive method. Data collection techniques used three ways, observation, interviews, and documentation studies. Then the collected data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that the achievement of the program has not yet shown the expected effectiveness due to the delay in disbursement of funds which has an impact on the delay in the implementation of activities and has not yet achieved the program objectives in fulfilling food and nutrition sources, especially for stunting so that it has not been able to contribute to helping Posyandu in providing animal protein in the stunting locus determined by the Mayor of South Tangerang. The integration indicator is not yet fully effective because there are still farm women groups that have not received intensive assistance from the program assistants. In addition, the implementation of P2L procedures applied in South Tangerang City has not been maximized because the concept of seedling houses is not suitable for the hot conditions in South Tangerang City. The adaptation indicator has not run optimally because the use of facilities and infrastructure for P2L activities is still limited to conventional agricultural tools.